Impact of VAT Changes on Different Types of Consumption Goods and Producers’ Prices - Macek, Jan; Kalíšková, Klára; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
Existing literature examining behavior of prices as a response to changes in VAT rate are somewhat ambiguous as to whether prices react before the implementation, after the implementation or both. This thesis analyzes response of consumer prices of different category goods in the Czech Republic and Slovakia between 2001 and 2018, and producer prices in CZE between 2004 and 2018. The chosen identification strategy uses linear regress model with specified control variables - fixed effects. The results show different outcomes across categories. Consumer prices of pork meat and meat products respond both before and after the implementation cumulatively. While consumer prices of poultry, beef meat, animal products, and legumes react only after the implementation of new VAT rate, consumer prices of dairy products only show preadoption effect. Almost the whole tax increase is reflected in consumer prices in CZE. Producer prices of cereal products and feed mixtures show only preadoption effect. Producers transferred 27 percent of the tax burden into their prices. In Slovakia, consumer prices of dairy products and pork meat are affected only in the first month after implementation of a VAT rate change. 22 percent of the new tax burden is transferred on consumers though consumer prices.
Vedoucí práce: Klára Kalíšková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses